Electrical properties of single CdTe nanowires - Matei, Elena; Florica, Camelia; Costas, Andreea; Toimil-Molares, María Eugenia; Enculescu, Ionut (Beilstein Journal of Nanotechnology, 2015)
Ion track, nanoporous membranes were employed as templates for the preparation of CdTe nanowires. For this purpose, electrochemical deposition from a bath containing Cd and Te ions was employed. This process leads to high aspect ratio CdTe nanowires, which were harvested and placed on a substrate with lithographically patterned, interdigitated electrodes. Focused ion beam-induced metallization was used to produce individual nanowires with electrical contacts and electrical measurements were performed on these individual nanowires. The influence of a bottom gate was investigated and it was found that surface passivation leads to improved transport properties.
Keywords: CdTe; electrodeposition; nanowires; transport properties

(untitled) - Li, D.; Xia, Y. (Adv. Mater., 2004)

(untitled) - Huang, M. H.; Mao, S.; Feick, H.; Yan, H.; Wu, Y.; Kind, H.; Weber, E.; Russo, R.; Yang, P. (Science, 2001)

(untitled) - Morales, A. M.; Lieber, C. M. (Science, 1998)

(untitled) - Lu, W.; Lieber, C. M. (Nat. Mater., 2007)

(untitled) - Cui, Y.; Wei, Q.; Park, H.; Lieber, C. M. (Science, 2001)

(untitled) - Yan, H.; Choe, H. S.; Nam, S.; Hu, Y.; Das, S.; Klemic, J. F.; Ellenbogen, J. C.; Lieber, C. M. (Nature, 2011)

(untitled) - Rogers, J. A.; Lagally, M. G.; Nuzzo, R. G. (Nature, 2011)

(untitled) - Martin, C. R. (Science, 1994)

(untitled) - Liang, H.-W.; Liu, S.; Yu, S.-H. (Adv. Mater., 2010)

(untitled) - Kline, T. R.; Tian, M.; Wang, J.; Sen, A.; Chan, M. W. H.; Mallouk, T. E. (Inorg. Chem., 2006)

(untitled) - Li, L.; Pan, S.; Dou, X.; Zhu, Y.; Huang, X.; Yang, Y.; Li, G.; Zhang, L. (J. Phys. Chem. C, 2007)

(untitled) - Matei, E.; Enculescu, I.; Toimil-Molares, M. E.; Leca, A.; Ghica, C.; Kuncser, V. (J. Nanopart. Res., 2013)

(untitled) - Toimil-Molares, M. E. (Beilstein J. Nanotechnol., 2012)

(untitled) - Lincot, D. (Thin Solid Films, 2005)

(untitled) - Matei, E.; Ion, L.; Antohe, S.; Neumann, R.; Enculescu, I. (Nanotechnology, 2010)

(untitled) - Jeong, S. S.; Mittiga, A.; Salza, E.; Masci, A.; Passerini, S. (Electrochim. Acta, 2008)

(untitled) - Hong, W.-K.; Song, S.; Hwang, D.-K.; Kwon, S.-S.; Jo, G.; Park, S.-J.; Lee, T. (Appl. Surf. Sci., 2008)

(untitled) - Sarkar, S.; Pal, S.; Sarkar, P. (J. Mater. Chem., 2012)

(untitled) - Florica, C.; Matei, E.; Costas, A.; Toimil Molares, M. E.; Enculescu, I. (Electrochim. Acta, 2014)

(untitled) - Kum, M. C.; Yoo, B. Y.; Rheem, Y. W.; Bozhilov, K. N.; Chen, W.; Mulchandani, A.; Myung, N. V. (Nanotechnology, 2008)